COMPLEXITY OR SIMPLICITY? COMPETITIVE REPERTOIRE AND FIRM PERFORMANCE IN UNCERTAIN CONTEXTS - Mwangi, Patricia (Archives of Business Research, 2019)
To survive in a changing environment, firms need to craft strategies that endow them with success. Competitive repertoire considers the full array of strategies deployed by an organization and provides a comprehensive view of the firm’s strategies. Deriving from the resource based view and the information processing theory, it is expected that by deploying a complex repertoire of competitive actions would secure superior performance for the firm due to the inability of other firms to mimic complex actions. However, it has been argued that in uncertain and dynamic environments, firms would benefit more by maintaining competitive repertoire simplicity thereby limiting themselves to a narrow set of known and familiar actions. These expectations were tested among 53 food and beverage manufacturing firms in Kenya. Primary data, collected using a structured questionnaire and secondary data were obtained and analyzed through ordinary linear regression. The study established that the food and beverage manufacturing firms largely relied on competitive repertoire simplicity which affected performance positively. The study therefore concluded that competitive repertoire simplicity was beneficial to firms in uncertain contexts and recommended that firms in such contexts maintain a narrow set of familiar actions.